Analysis of Comparative Advantages and Shifts Share in Economic Sectors: Empirical Study in Wajo Regency, Indonesia - Aditya Halim Perdana Kusuma Putra; R. Rahmi (Manunggal Halim Jaya, 2023)
The aims of this research are: (1) to analyze the growth classification of economic sectors in the Wajo Regency 2011-2015; (2) to analyze the basic sector of the economy in the Wajo Regency 2011-2015; (3) to analyze the share and shifts in the economy sector Wajo Regency 2011-2015. This study uses secondary data obtained from BPS-Statistics South Sulawesi Province, BPS-Statistics Wajo, and the Department of Planning and Regional Development Wajo. Data were analyzed using Klassen Typology, Location Quotient, and Shift-Share analysis. The results of this research show that: (1) Sector classified as a developed sectors in the Wajo Regency is The of Agriculture, Forestry and Fisheries, and sector mining and excavation. (2) sectors is a basic sector of Wajo Regency is the sector of Agriculture, Forestry and Fisheries, sector mining and excavation, sector Procurement Electricity and Gas, the sector of Wholesale and Retail, Car Repair, and Motorcycles, (3) The structure of the Wajo Regency 2011-2015 start forward to slide in the economic sector from primer sector to secondary sector (4). The sectors that have competitive advantages (D) in Wajo are sectors of Agriculture, Forestry and Fisheries, sector Procurement Electricity and Gas, construction sector, sectors Transportation and Warehousing, sector Provision of Accommodation and Food Drink, the Financial Services sector and the insurance sector, Real Estate sector, Service sector Corporate sector Public Administration, Defense, and Social Security Mandatory, and sector service of education.